Assessing the Role of the Coach in Terms of Dropping out from Youth Sports - Szakál, Zsolt (Central European Journal of Educational Research, 2022)
Much of international research deals with the subject, so we can say that probably one of the most important issues in the field of youth education today is to explore the causes of early drop-out from organised sport. The aim of this essay was to test our self developed measurement tool and gain insight into what coaches see as causes of dropping out within their own sport and what percentage of this phenomenon is experienced in their field. The main question for us is, why junior athletes between the age of 13–16 are dropping out of competitive sports, what role the coach’s personality has (in this), and what other reasons might the phenomenon have. In our enquiry, we sought to find out the opinion of coaches of team sports such as handball, football or icehockey, in addition to individual sports, like athletics and karate. In the research, we used only certain parts of the interviews during the analysis, paying special attention to the coaching attitude, the coach-athlete relationship, and the ways of motivation and methods used by the coach. The results confirmed that the causes of dropout should be sought for in the dimensions which we set up earlier. In the respect of the exploratory nature of the study, we cannot draw far-reaching conclusions, but we certainly consider it as a good starting point for our further research.